2007
DOI: 10.1113/jphysiol.2007.132902
|View full text |Cite
|
Sign up to set email alerts
|

Glucose kinetics and exercise tolerance in mice lacking the GLUT4 glucose transporter

Abstract: The absence of GLUT4 severely impairs basal glucose uptake in vivo, but does not alter glucose homeostasis or circulating insulin. Glucose uptake in isolated contracting skeletal muscle (MGU) is also impaired by the absence of GLUT4, and onset of muscle fatigue is hastened. Whether the body can compensate and preserve glucose homeostasis during exercise, as it does in the basal state, is unknown. One aim was to test the effectiveness of glucoregulatory compensation for the absence of GLUT4 in vivo. The absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 46 publications
(57 reference statements)
3
51
0
Order By: Relevance
“…[17][18][19][20][21][22][23][24]. In response to an 18-hour fast, hepatic ATP, ADP, and AMP levels were decreased, unchanged, and increased, respectively, resulting in a nearly 6-fold increase in AMP/ATP ratios compared with fed mice and mice fasted for 5 hours ( Figure 1A).…”
Section: Metabolic Stress Induces Dramatic Changes In Hepatic Adeninementioning
confidence: 98%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23][24]. In response to an 18-hour fast, hepatic ATP, ADP, and AMP levels were decreased, unchanged, and increased, respectively, resulting in a nearly 6-fold increase in AMP/ATP ratios compared with fed mice and mice fasted for 5 hours ( Figure 1A).…”
Section: Metabolic Stress Induces Dramatic Changes In Hepatic Adeninementioning
confidence: 98%
“…Our goals, therefore, were to test the hypotheses that (a) reductions in the hepatic energy state are a physiological phenomenon not isolated to exhaustive exercise and (b) glucagon receptor activation mediates a lowered hepatic energy state sufficient to activate AMPK through a process requiring cytosolic phosphoenolpyruvate carboxykinase (PEPCK-C). The foundation for this latter hypothesis is that a rise in plasma glucagon is characteristic of metabolic stress (17)(18)(19)(20)(21)(22)(23)(24) and increased hormone levels are shown to amplify phosphorylation of AMPK in vitro and in perfused liver (25,26). Studies in vivo have also shown that hepatic glucagon action is the primary determinant of gluconeogenesis via PEPCK-C and stimulation of coupled pathways, including fatty acid activation and ureagenesis, which are required to offset higher glucose use in the body during exercise (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insulin clamp protocol can also be modified to allow for glucose levels to fall to relative hypoglycemia to assess counter-regulatory response 2,23,24 . Arterial catheterization can also be used to assess the dynamics of glucose metabolism during exercise [25][26][27][28][29][30] . This is significantly advantageous over conventional approaches conducted at single time points pre-and post-exercise or in isolated muscles ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The R g response to exercise was diminished in mice with a partial HK II knockout . A heterozygous deletion of GLUT4 did not impair R g in working muscle (Fueger et al, 2004b); however, a complete deletion of GLUT4 prevented the increase in R g with exercise and led to marked hyperglycemia (Fueger et al, 2007b). We tested the hypothesis that if the glucose phosphorylation barrier in GLUT4 knockout mice was lowered by HK II overexpression, muscle would then be sensitive to reduced transport capacity.…”
Section: Glucose Phosphorylation Within the Working Muscle Cellsmentioning
confidence: 99%